Stepwise School Opening and an Impact on the Epidemiology of COVID-19 in the Children - Yoon, Yoonsun; Kim, Kyung-Ran; Park, Hwanhee; Kim, Soyoung; Kim, Yae-Jean (Journal of Korean medical science, 2020)
Data on severe acute respiratory syndrome coronavirus-2 transmission from a pediatric index patient to others at the school setting are limited. Epidemiological data on pediatric coronavirus disease 2019 (COVID-19) cases after school opening are warranted. We analyzed data of the pediatric patients with COVID-19 collected from the press release of the Korea Centers for Disease Control and Prevention. Information on the school opening delay and re-opening policies were achieved from the press release of the Korean Ministry of Education. The school openings were delayed three times in March 2020. Online classes started from April 9, and off-line (in-person) classes started from May 20 to June 8 at four steps in different grades of students. There was no sudden increase in pediatric cases after the school opening, and the proportion of pediatric cases among total confirmed cases in the nation around 7.0%. As of July 31, 44 children from 38 schools and kindergartens were diagnosed with COVID-19 after off-line classes started. More than 13,000 students and staffs were tested; only one additional student was found to be infected in the same classroom. The proportions of pediatric patients without information on infection sources were higher in older age groups than in younger age groups (17.4% vs. 52.4%, = 0.014). In the younger age group, 78.3% of children were infected by family members, while only 23.8% of adolescents in the older age group were infected by family members ( < 0.001). Korea had a successful transition from school closure to online and off-line school opening, which did not cause significant school-related outbreak among the pediatric population.